Cashing in on cyberpower : how interdependent actors seek economic outcomes in a digital world - Peters, Mark T., II (Potomac Books, an imprint of the University of Nebraska Press, 2018)
As the world has become increasingly digitally interconnected, military leaders and other actors are ditching symmetric power strategies in favor of cyberstrategies. Cyberpower enable actors to change actual economic outcomes without the massive resource investment required for military force deployments. Cashing In on Cyberpower addresses the question, Why and to what end are state and nonstate actors using cybertools to influence economic outcomes? The most devastating uses of cyberpower can include intellectual property theft, espionage to uncover carefully planned trade strategies, and outright market manipulation through resource and currency values. Offering eight hypotheses to address this central question, Mark T. Peters II considers every major cyberattack (almost two hundred) over the past ten years, providing both a quick reference and a comparative analysis. He also develops new case studies depicting the 2010 intellectual property theft of a gold-detector design from the Australian Codan corporation, the 2012 trade negotiation espionage in the Japanese Trans-Pacific Partnership preparations, and the 2015 cyberattacks on Ukrainian SCADA systems. All these hypotheses combine to identify new data and provide a concrete baseline of how leaders use cybermeans to achieve economic outcomes. -- Provided by publisher.